Adaptive robust precision motion control of high-speed linear motors with on-line cogging force compensations - Bin Yao; Chuxiong Hu; Qingfeng Wang (2007 IEEE/ASME international conference on advanced intelligent mechatronics, 2007)
This paper studies the precision motion control of high-speed/acceleration linear motors in a commercial gantry which are subject to significant nonlinear cogging forces. A discontinuous projection based desired compensation adaptive robust controller (ARC) is constructed and implemented. Design models consisting of known basis functions with unknown weights are used to approximate various unknown nonlinear forces with model approximation errors being explicitly accounted for in the controller design process. On-line parameter adaptation is then utilized to reduce the effect of various parametric uncertainties while certain robust control laws are synthesized to effectively handle various modeling uncertainties for a guaranteed robust performance. Comparative experimental results obtained on an Anorad commercial gantry with a linear encoder resolution of 0.5 mu m and a position measurement resolution of 20 nanometers by external laser interferometers are presented to illustrate the achievable control performance of the proposed control strategy in implementation. Experiments are also performed to explicitly identify the cogging forces via external force sensors. Various comparative experimental results with and without the proposed cogging force compensations are then obtained to validate the effectiveness of the approach in practical applications.